Community structures of benthic macroinvertebrates in intermittent stream, Sakaerat environmental research station, Wang Nam Khiao District, Nakhon Ratchasrima Province - เทวาภวัต, ปฏิพัทธ์; แสงประดับ, นฤมล (KKU Science Journal, 2017)
Community structures of benthic macroinvertebrates were investigated in Thum Jon Aung, Sakaerat environmental research station, Wang Nam Khiao District, Nakhon Ratchasrima Province during December 2014 to December 2015. Water samples, benthic macronvertebrates and adult stage of aquatic insects were collected monthly in order to observe changing of physicochemical characters of stream and benthic macroinvertebrates community within 13 months. It was found that Thum Jon Aung is an intermittent stream where dissolved oxygen was very low. It could be divided based on physical characteristics into 4 phases included filling, dry, re-filling and flow phases. A total of 7,592 individuals in 2 phyla, 11 orders, 39 families and 60 genera were identified. Diversity and evenness of benthic macroinvertebrates in the re-filling phase were higher than those of flow, dry and filling phases, respectively. Blackfly larvae were pioneer species at initial of flow phase and were succeeded by mayfly, stonefly and caddisfly larvae. Tolerant taxa such as gastropods, dipteran larvae, water beetles, water bugs and dragonfly nymphs were increase after the water ceased flow. Allochthounous were main energy source. We suspected that some benthic macroinvertebrates may refuge in crevice during the non-flow period and drift to downstream during the flow period. Drift of immature stages and aerial dispersal of adults were the main mechanism for colonization. Therefore, intermittent stream may play an important role as a refuge and genetic resources of aquatic organisms.